Theory of mind and its relationship with alexithymia and quality of life in patients with psychogenic nonepileptic seizures: Comparisons with generalised epilepsy and healthy controls - MİDİ, İPEK; ERGÜN, SERHAT; GÜRSOY, SÜHA CAN; TOPÇUOĞLU, VOLKAN (W B SAUNDERS CO LTD, 2021)
Objective: Psychogenic nonepileptic seizures (PNES) are associated with high alexithymia, social cognition problems and low quality of life (QoL). Theory of Mind (ToM) has been studied in several conditions as a significant predictor of QoL. We aimed to assess the relationship between ToM abilities, alexithymia and subjective QoL in PNES patients and compare with generalised epilepsy (ES) patients and healthy controls. Method: Patients with PNES (n = 28), ES (n = 28) and healthy volunteers (n = 28) were evaluated for alexithymia and quality of life (QoL) with Toronto Alexithymia Scale-20 (TAS-20) and Short Form-36 (SF-36). Reading the Mind in the Eyes test was used for assessment of affective ToM and Hinting Task and Strange Stories tests for cognitive ToM abilities. Results: Analyses revealed lower SF-36 scores and poorer ToM performance in the PNES group compared to healthy group and poorer cognitive ToM performance than ES group. Cognitive ToM performance was inversely correlated with TAS-20 difficulty identifying feelings subscale and physical functioning subscale of SF-36 in the PNES group. Conclusion: These results are consistent with previous research on PNES and other somatoform disorders and suggest that PNES is associated with impaired ToM task performance. ToM task performance might be related to specific aspects of alexithymia and QoL.
Keywords: Psychogenic seizures; Alexithymia; Theory of mind; Social cognition; Quality of life; SOCIAL COGNITION; EMOTIONAL AWARENESS; CHILDHOOD TRAUMA; PREVALENCE; SCALE; SCHIZOPHRENIA; DISSOCIATION; RECOGNITION; RELIABILITY; ABILITIES